DEBRIS FLOW EVENT OF 2014 AND ITS IMPACT ON THE ACCUMULATION OF THE SOLID FRACTION IN THE KYNGARGA RIVER CHANNEL, TUNKA VALLEY, SOUTHWESTERN CISBAIKALIA, RUSSIA - A. V. Kadetova; A. A. Rybchenko; E. A. Kozyreva; Yongbo Tie; Huayong Ni (Геодинамика и тектонофизика)
On 28 June 2014, debris flows brought large volumes of loose material into the Kyngarga river valley. The material was sourced from rock collapse and rock sliding on the valley slopes and delivered mainly to the river by debris flows from the side valleys of the river basin. Our field studies and analysis of the satellite images revealed that the potential debris volume received by the river amounted to about 1×106 m3. The morphometric parameters of the Kyngarga river basin are favorable for the river-channel processes associated with floods, debris flows and waterrock flows.